2015
DOI: 10.1101/lm.038216.115
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial hippocampal θ-state differentiates single-unit response profiles during rabbit trace eyeblink conditioning

Abstract: Eyeblink conditioning given in the explicit presence of hippocampal u results in accelerated learning and enhanced multipleunit responses, with slower learning and suppression of unit activity under non-u conditions. Recordings from putative pyramidal cells during u-contingent training show that pretrial u-state is linked to the probability of firing increases versus decreases rather than to the magnitude of such responses. These findings suggest that the learning facilitation during u may be due to the recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
1
4
1
Order By: Relevance
“…Utilizing the same four groups (T+, T−, T+ yoked, and T− yoked), Griffin et al ( 28 ) showed that T− animals required significantly more trials to reach early (fifth CR) and late (8/9 CRs) learning criteria, demonstrated a lower percentage of CRs on the first 4 days of training, and required more trials to reach fifth CR than their yoked control counterparts. These results have been replicated by our lab with T− animals reaching the fifth CR criterion later than T+ animals ( 146 , 147 ) and T− animals showing a lower percentage of CRs across the first 4 days of training ( 148 ). Taken together, the deficits seen in both delay and trace EBC mirror the patterns seen in patients and animal models of several psychiatric disorders.…”
Section: Theta-triggered Modelsupporting
confidence: 62%
See 3 more Smart Citations
“…Utilizing the same four groups (T+, T−, T+ yoked, and T− yoked), Griffin et al ( 28 ) showed that T− animals required significantly more trials to reach early (fifth CR) and late (8/9 CRs) learning criteria, demonstrated a lower percentage of CRs on the first 4 days of training, and required more trials to reach fifth CR than their yoked control counterparts. These results have been replicated by our lab with T− animals reaching the fifth CR criterion later than T+ animals ( 146 , 147 ) and T− animals showing a lower percentage of CRs across the first 4 days of training ( 148 ). Taken together, the deficits seen in both delay and trace EBC mirror the patterns seen in patients and animal models of several psychiatric disorders.…”
Section: Theta-triggered Modelsupporting
confidence: 62%
“…Using our BCI, we have shown that training in the explicit absence of hippocampal theta produces deficits in EBC expected of a number of psychiatric conditions. Furthermore, these behavioral deficits are accompanied by electrophysiological disruptions at the LFP ( 147 , 148 ), multiple- ( 28 , 147 ), and single-unit ( 146 ) levels that are characteristic of conditions as disparate as schizophrenia, MDD, and AD. Of particular interest are the patterns seen across the regions necessary for EBC, with a lack of synchrony between hippocampus and cerebellum ( 148 ) and the absence of relevant response patterns in mPFC units ( 147 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theta oscillations are also important in acquisition and retention of hippocampal‐dependent tasks (Hoffmann, Cicchese, & Berry, ; Takehara‐Nishiuchi et al, ). In fact, Berry et al reported that presenting trials when theta power is high results in faster learning of trace (or delay) EBC as compared with presenting trials when theta is not present (Cicchese, Darling, & Berry, ; Seager, Johnson, Chabot, Asaka, & Berry, ). Failures to replicate this effect may be due to presentation of the conditioning stimuli at a sub‐optimal phase of the theta cycle (Nokia, Waselius, Mikkonen, Wikgren, & Penttonen, ), hence an analysis of theta phase and phase resetting is important.…”
Section: Introductionmentioning
confidence: 99%